The effectiveness of silver nanoparticles as a clean-up material for water polluted with bacteria DNA conveying antibiotics resistance genes: Effect of different molar concentrations and competing ions - Adaora S. Ezeuko; Mike O. Ojemaye; Omobola O. Okoh; Anthony I. Okoh (Elsevier, 2022)
This study employed silver nanoparticles to remove DNA conveying antibiotic resistance genes from water. Three different molar concentrations of silver nanoparticles represented as BD1 (0.1 M), BD2 (0.5 M), and BD3 (1.0 M) were synthesized as adsorbents and evaluated in a batch adsorption system for the removal of bacteria DNA conveying antibiotic resistance genes from simulated aqueous solution. The authenticity of the adsorbents was confirmed by characterization techniques using Fourier transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM) coupled with energy-dispersive x-ray spectroscopy (EDX), and x-ray diffraction spectroscopy (XRD) indicated the successful synthesis of these AgNPs. Adsorption studies involving the different operating conditions on the synthesized materials showed that pH affects the removal of DNA with increased removal efficiency observed at acidic pH (removal percentage ranging from 50.26-87.61%, 65.80-87.79%, and 69.23-87.92% for BD1, BD2, and BD3 respectively). Maximum adsorption equilibrium was achieved after 180, 195, and 225 mins for BD1, BD2, and BD3. The isotherm study revealed that Langmuir model is the best fit compared to Freundlich model with highest correlation coefficient and reduced Chi-square (X2) of R2 = 0.97625 and X2 = 0.12142, R2 = 0.96049 and X2 = 0.24403, R2 = 0.85108 and reduced X2 = 1.00914 for BD1, BD2, and BD3 respectively. The kinetic study for the adsorption process indicates that the adsorption of bacteria DNA onto AgNPs obeyed pseudo-second-order with the highest R2 values (ranging from 0.90 to 0.98). Similarly, competing ions (cations and anions) influenced the adsorption capacity in this study. Therefore, this study concludes that AgNPs demonstrated effectiveness in removing bacteria DNA-conveying ARGs from water and will serve as an excellent option to tackle the menace of ARGs in water.